2008
DOI: 10.1111/j.1349-7006.2008.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic signaling in bufalin‐ and cinobufagin‐treated androgen‐dependent and ‐independent human prostate cancer cells

Abstract: Prostate cancer has its highest incidence in the USA and is becoming a major concern in Asian countries. Bufadienolides are extracts of toxic glands from toads and are used as anticancer agents, mainly on leukemia cells. In the present study, the antiproliferative and apoptotic mechanisms of bufalin and cinobufagin on prostate cancer cells were investigated. Proliferation of LNCaP, DU145, and PC3 cells was measured by 3-(4,5-dimethylthiazol-2-yle)-2,5-diphenyltetrazolium bromide assay and the doubling time (tD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 43 publications
9
107
2
Order By: Relevance
“…Similar to the present findings for arenobufagin, certain studies have reported that bufalin, another representative cardiac glycoside compound from secreted toad toxins, inhibited cell proliferation in various cancer cells and induced apoptosis and cell cycle arrest in PC cells (21,(39)(40)(41). The exact mechanism by which arenobufagin induces apoptosis in pancreatic cells is unclear.…”
Section: Discussionsupporting
confidence: 74%
“…Similar to the present findings for arenobufagin, certain studies have reported that bufalin, another representative cardiac glycoside compound from secreted toad toxins, inhibited cell proliferation in various cancer cells and induced apoptosis and cell cycle arrest in PC cells (21,(39)(40)(41). The exact mechanism by which arenobufagin induces apoptosis in pancreatic cells is unclear.…”
Section: Discussionsupporting
confidence: 74%
“…Bufalin isolated from Chansu was reported to have the activity of inducing apoptosis in cancer cells such as human prostate, hepatocellular, endometrial and ovarian cancer cells and leukemia cells. (Gu et al 2007;Takai et al 2008;Watabe et al 1996;Yu et al 2008). However, whether or not bufalin has inhibitory activity against the proliferation of human NSCLC cells and its molecular mechanisms of action are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that bufalin suppress cell proliferation and cause apoptosis in prostate cancer cells via a sequence of apoptotic modulators, including Bax, cytochrome c, and caspases. The upstream mediators might be p53 and Fas in androgen-dependent LNCaP cells and Fas in androgen-independent DU145 and PC3 cells (Yu et al, 2008).…”
Section: Prostate Cancermentioning
confidence: 99%